(3GdeQGLYI Hjf GdJfXjQ hGdJWHjbs - (3eMeO SejQ(B, (3GdUHGfs ((3HjQhJ(B:s (3GdOGQ GdLGeYjI(B,s, 1990)
(3HjFI Yed GdeQGLY(B- (3fMh GjLGO fXQjI ddeQGLYI(B- (3eYGjjQ Ch eSJhjGJ GdeQGLYI(B- (3eSDhdjI GdeQGLY(B- (3JbQjQ GdeQGLY GdNGQLj(B- (3GdLhGfH GdafjI dENJHGQGJ GdeQGLY(B- (3GdQbGHI GdOGNdjI(B- (3GdLhGfH GdejOGfjI dYedjI GdeQGLYI hELQGAGJ GdJMbb(B.s
Keywords: (3GdeMGSHIs; (3GdeQGLYIs